Solve by using quadratic formula: 3x^2 + 6x + 2 = 0

### 1 Answer | Add Yours

The equation 3x^2 + 6x + 2 = 0 has to be solved.

The solution of a quadratic equation of the form ax^2 + bx + c = 0 is `(-b+-sqrt(b^2-4ac))/(2a)`

For the given equation a = 3 , b = 6 and c = 2.

The roots of the equation are `(-6+-sqrt(36-24))/6 = -1 +- 1/sqrt 3`

**The roots of 3x^2 + 6x + 2 = 0 are **`-1 +- 1/sqrt 3`

### Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes